Catalysts evaluation for production of hydrogen gas and carbon nanotubes from the pyrolysis-catalysis of waste tyres. (26th July 2019) - Li, Wenping; Wei, Mimi; Liu, Yunquan; Ye, Yueyuan; Li, Shuirong; Yuan, Wenqiao; Wang, Meng; Wang, Duo
Abstract: Six different types of catalysts (nickel, iron, and cobalt each supported by γ-Al2 O3 and activated carbon) that were prepared via impregnation were used to produce hydrogen (H2 ) and carbon nanotubes (CNTs) from the pyrolytic product of waste tyres. A two-stage pyrolytic-catalytic reactor was constructed, in which the waste tyre was pyrolyzed in the first pyrolysis reactor, and the resultant pyrolysis vapors underwent the reforming and upgrading step in the downstream catalytic reactor. The results showed that the interaction between the active metal and its support had a remarkable effect on the production of H2 and CNTs. Compared with the series of γ-Al2 O3 supported catalysts, all the activated carbon-supported catalysts showed higher H2 yields and better CNTs quality. For the same catalyst support (γ-Al2 O3 or activated carbon), the higher yield of H2 and better quality of CNTs were obtained by the Ni catalysts, followed by the Fe catalysts and the Co catalysts. Among all the catalysts, Ni supported by activated carbon exhibited the best catalytic performance, producing the highest hydrogen yield (59.55 vol.%) and the best CNT quality. Further investigation about the influence of CH4 and naphthalene as the carbon source on generated CNTs revealed that CH4 led to longer CNT length and higher graphitization than naphthalene. Graphical abstract: Image 1 Highlights: Six catalysts were evaluated for producing H2 and CNTs using tyre as precursor. AC supported catalysts showed higher H2 yields and better CNTs quality. Ni/AC exhibited the best catalytic performance producing the highest H2 yield and the best CNT quality. CH4 as the carbon sources led to longer CNT length and higher graphitization than naphthalene.